Differential impacts of water diversion and environmental factors on bacterial, archaeal, and fungal communities in the eastern route of the South-to-North water diversion project - Moran Tang; Qian Chen; Xinzong Xiao; Yitao Lyu; Weiling Sun (Environment International)
Water diversion projects effectively mitigate the uneven distribution of water resources but can also influence aquatic biodiversity and ecosystem functions. Despite their importance, the impacts of such projects on multi-domain microbial community dynamics and the underlying mechanisms remain poorly understood. Utilizing high-throughput sequencing, we investigated bacterial, archaeal, and fungal community dynamics along the eastern route of the South-to-North water diversion project during both non-water diversion period (NWDP) and water diversion period (WDP). Our findings revealed competitive exclusion effects among bacterial and archaeal communities during the WDP, characterized by decreased species richness and increased biomass, while fungal biomass significantly declined. Distance-decay relationships suggested microbial homogenization during the WDP. Robustness analyses revealed reduced community stability during the WDP, with water diversion primarily influencing bacterial stability, while environmental factors had a greater impact on archaeal and fungal communities. Stochastic processes, primarily homogenizing dispersal and drift, intensified for bacterial and fungal communities during the WDP. Notably, only bacterial functional diversity decreased during the WDP, with increased relative abundance of chemoheterotrophic and organic compound catabolic bacteria and declined photoautotrophic bacteria. PLS-PM indicated that water diversion primarily shaped bacterial assembly processes and functional guilds, whereas environmental factors had a greater influence on archaeal communities. This study enhances our understanding of microbial dynamics during the WDP and underscores the importance of assessing both direct impacts and resulting environmental fluctuations.